Capacitación a docentes de educación regular sobre el enfoque auditivo oral para mejorar la inclusión educativa de los niños con implante coclear que asisten al centro ecuatoriano de audición y lenguaje de la ciudad de Loja, en el periodo marzo –julio 2015. - Costa Pacheco, Oscar Ivan (2016)
This research includes a study on the EDUCATION ON AN ORAL HEARING APPROACH TO IMPROVE THE INCLUSION OF CHILDREN WITH COCHLEAR IMPLANTS THAT ATTEND THE ECUADORIAN CENTER OF HEARING AND LANGUAGE, CEAL IN THE SCHOOL YEAR OF JULY 2014 - 2015. The methods used in this work were: scientific, analytical synthetic, hermeneutical and statistical method. The technique used was the observation and also survey instruments were designed for this purpose. 5 teachers were involved and also directly participated in this research, the study mainly targeted to the regular school system in which the students were involved. The study shown that teachers which with a special training performed a bit better than the rest that did not take this course on special needs. The research also presented as a final recommendation that it is necessary to foster and strength teacher skills in order to provide and education of quality.